2009
DOI: 10.1007/s00540-009-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

Insertion length and resistance during advancing of epidural catheter

Abstract: At approximately 2.5 cm in the epidural space, advancing an epidural catheter causes resistance. Further advancing past this point may cause migration of the catheter into the vessels, or the coiling of the catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…18 Other studies have shown that limiting the length of catheter inserted into the epidural space to less than 3 to 5 cm may help avoid knotting and kinking. 2,11,16,17 Once the catheter is properly inserted, locating the tip in the epidural space continues to be a challenge. Using electrical stimulation of 1 to 10 mA, a motor response in the lower extremities has been shown to correlate with the location of the catheter in the epidural space.…”
Section: Discussionmentioning
confidence: 99%
“…18 Other studies have shown that limiting the length of catheter inserted into the epidural space to less than 3 to 5 cm may help avoid knotting and kinking. 2,11,16,17 Once the catheter is properly inserted, locating the tip in the epidural space continues to be a challenge. Using electrical stimulation of 1 to 10 mA, a motor response in the lower extremities has been shown to correlate with the location of the catheter in the epidural space.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Kundra et al [1] regarding resistance to the insertion of epidural catheter and intravascular placement. It is interesting to note that resistance was felt in a large number of patients in the study (83 out of 120; 69.12%) at insertion length of 2.5 cm during the epidural catheter placement.…”
Section: To the Editormentioning
confidence: 99%